Theoretical and Conceptual Considerations for Analyzing Social Interfaces in Agroecosystems - Gallardo-López, Felipe; Linares-Gabriel, Ariadna; Hernández-Chontal, Mario Alejandro (Frontiers in Sustainable Food Systems, 2021)
The current framework of agroecosystem (AES) knowledge focuses on a systemic approach or static structures rather than on dynamic processes that are defined historically. The hypothesis is that agroecosystems are the product of the interdependence of a diversity of actors (present and absent) and, therefore, constitute complex social interfaces, which, in order to address them, require a new understanding of the centrality of the actors and their capacity for agency. Then, regarding this complexity, some aspects are not clearly defined in the systemic approach which need to be more explicit such as: (a) the implicit psychosocial aspects and (b) the relationships with their social environment, how these affect them and are affected by them. The purpose of this document is to suggest a theoretical and conceptual approach to correct these unclear areas. First, the centrality of actors (including their agency capacity) in the AES is recognized. Besides, their interdependence with the diversity of actors (present and absent) and therefore the need to analyze the AES complex social interfaces.